Fabrication and characterization of hydrogel microparticulate drug delivery system - Ma, Liding (2009)
In this project, the stretched cavity-assisted molding of particles (SCAMP) method was applied to fabricate microparticulate drug delivery system (DDS) aiming at growth factors delivery. SCAMP is a top-down technique involving the usage of patterned mold and ultraviolet (UV) curable precursor hydrogel solution, a special stretched cavity-assisted particle demodeling mechanism and a freeze-peel harvest method. Optimization of the fabrication procedures to increase the particle yield was also an important effort in this project. Cavity filling efficiency and harvest efficiency were the two issues studied to realize this target. To evaluate the inertness of SCAMP fabrication procedures to fragile protein drugs, the bioactivity test experiment was also carried out, by first culturing smooth muscle cells in three kinds of media with two containing either release or stock-prepared growth factors and the third containing growth factor, and the applying dimenthylthiazol diphenylterazolium bromide (MTT) assay to quantify the cell viability as indication to bioactivity status of the drugs. The results showed that the growth factors released from SCAMP fabricated particles highly retained their bioactivity. Finally, a set of experiment was conducted to evaluated the SCAMP fabricated DDS’s ability to provide sustained and variable drug release. The results showed that this DDS can release the model basic fibroblast growth factor (BFGF) in a sustain manner as long as four weeks without serious burst release in the first 24 hours. Longer UV exposed particles did not significantly change the release dose level compared to the normally fabricated particle, while particles encapsulated by biodegradable polymer film significantly reduced the released dose level for about 14 days, indicating its potential to delay the drug release for a certain period.